History Learning and Digital Tourism: Utilizing AI for Cultural Conservation in the Ijen Geopark Area for High School Students in Banyuwangi - Mahfud; Triana Kartika Santi; Riztika Widyasari; I Wayan Pardi (Mimbar Ilmu, 2025)
This research is motivated by the problem of low integration of the potential for local culture-based education in Ijen Geopark in history learning at the secondary school level, which is still predominantly text-based and has minimal use of interactive technology. The purpose of this research is to develop history learning modules based on digital tourism, AI, and AR to improve students' understanding of local history while fostering cultural conservation attitudes. The research subjects included 190 students and 8 history teachers who were selected through stratified random sampling. The research method used is Research and Development (R&D) with preliminary study stages, product design, expert validation, limited trials, and effectiveness tests. Data collection techniques are carried out through tests, questionnaires, observations, and interviews, while data analysis techniques include content validity tests, paired t-tests, chi-squares, ANOVAs, and Pearson correlation analysis. The results showed a significant increase in local history knowledge (the average pre-test score of 48.2 increased to 75.6 in the post-test, p < 0.001), a more positive attitude of cultural conservation, expert validation with a very feasible category (content 90.1% and media 88.4%), and teacher perception that strongly supports the implementation of modules in history learning based on local contexts.